Pengaruh Suhu dan Waktu Penyeduhan Teh Daun Kelakai (Stenochlarna Palutris) Dengan Treatmen Asam Lemon (Citrus Limon) Terhadap Kadar Besi (Fe) - Husnul Chotimah; Ayutha Wijinidyah; Jerry Selvia; Susan E Lumban Gaol (Jurnal Sylva Scienteae, 2024)
Iron (Fe) is one of the many nutrients found in kelakai. Lemon acid treatment (Citrus lemonade) is used in the processing of kelakai tea powder as an effort to increase the nutritional value of the plant. The aim of this research is to determine how temperature and brewing time affect the iron (Fe) content in kelakai leaf tea (Stenochlarna palutris) prepared with lemon acid (Citrus lemonade). This research used a 2 factorial completely randomized design (CRD) and was experimental. There are two factors: the first is the temperature at which the brewing is done (40, 50 and 60 degrees Celsius), and the second is the brewing time (1, 5 and 10 minutes) with three repetitions. Two-Way Analysis of Variance (ANOVA) was used in data analysis, along with an additional 5% Honestly Significant Difference (BNJ) test. These findings show a very significant influence of brewing temperature, brewing time, and the combination of temperature and brewing time. The results of the research show that moderate temperatures produce high iron (Fe) levels, moderate brewing results in high iron (Fe) levels. The brewing temperature treatment T2 (50oC) had the highest amount of calcium at 2.73778 ppm. Iron (Fe) levels are low at temperature T1 (400C) of 1.42000 ppm.  The effect of brewing time on high iron (Fe) levels at F2 time (5 minutes) is 2.73778 ppm. The lowest iron (Fe) content was located at the longest brewing time, namely F3 (10 minutes) at 1.12267 ppm. T3F2 (600C, 5 Minutes) with iron (Fe) content of 3,707 ppm.  The treatment that produces the lowest iron (Fe) content is T2F3 (500C, 10 minutes) with a value of 0.702 ppm